Role of Green Taxes on Economic Growth Goals of Sustainable Development Directly and Through Environmental Performance: A System GMM Approach - Onur Şimşek; Gülçin Kaya İnceiplik (Journal of Economy Culture and Society)
Based on the UN’s Millennium Development Goals, the Sustainable Development Goals (SDGs) are a global call to action that have led to structural changes in the means and objectives of countries’ economic policies since 2016. This study examines green tax policies that are crucial for achieving environmental goals and analyzes the impact thereof on economic goals. The role of green taxes in sustainable development is determined by analyzing the data of 32 selected Organisation for Economic Co-operation and Development (OECD) countries for 2000–2019 with the system generalized method of moments (GMM) approach. The model indirectly focuses on CO emissions per capita and econometrically analyzes the impact of green tax revenues on the growth rate of real GDP per capita. Moreover, this study was evaluated in light of the double dividend debate. The study results suggest that green taxes contribute to environmental efficiency and offer empirical evidence on economic sustainability indicators. Furthermore, as the ratio of green tax revenues in GDP increases in the selected countries, the economic goals of sustainable development are closer and the positive effect increases as the CO2 amount per capita decreases. In conclusion, harmonizing the basic principles of environmental policies with fiscal policies is crucial for combating environmental problems and for national economies.